The significance of mitochondrial respiratory function in regulating oxygen uptake and performance in humans - Cardinale, D. A. (Avhandlingsserie för Gymnastik- och idrottshögskolan, 14, 2018)
The mitochondrion is one of the most fascinating organelles of our cells which has kept and keeps researchers busy in studying its origin, the complex morphology, the numerous functions, the rapid adaptations to a variety of stimuli and its role in health and disease. Exercise challenges cellular homeostasis and skeletal muscle mitochondria greatly adapt to repeated bouts of exercise by increasing mitochondrial respiratory function and content to match energy requirements and to better sustain future perturbations induced by muscle contractions. The oxidative capacity of mitochondria has been shown to exceed the capacity of the cardiorespiratory system to supply oxygen to active muscle at maximal exercise intensity. Despite this, exercise training further increases this overcapacity. Little is known about the role of this excess oxidative capacity of mitochondria in regulating oxygen consumption, the role of oxygen delivery in determining exercise-induced skeletal muscle adaptations, and whether any sex-related differences exist. The assessment of mitochondrial respiratory function in high resolution respirometer is largely used for clinical and scientific purposes. However, the reliability of this method has not been systematically investigated and warrant further investigation.